2020
DOI: 10.15376/biores.15.3.6617-6626
|View full text |Cite
|
Sign up to set email alerts
|

Variation of quantitative anatomical characteristics in the culm of belangke bamboo (Gigantochloa pruriens)

Abstract: The anatomical characteristics of the stem of belangke bamboo (Gigantochloa pruriens), which is native in North Sumatra, Indonesia, were examined to attain valuable information for identification and effective utilization. The number and type of vessel bundles and the fiber and metaxylem dimensions in the longitudinal (bottom, middle, and top) and radial (outer, central, and inner) directions of the bamboo culm were investigated by optical microscopy. The vascular bundles were distributed unevenly and arranged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 8 publications
4
18
0
Order By: Relevance
“…Vessel cell portion tended to increase from the bottom culm to the top culm position. Darwis et al (2020) reported a similar trend in G. pruriens, with an increase in the parenchyma percentage from the outer to the inner part and vice versa for the vascular bundles. They also reported that parenchyma percentage in the bottom position was lower than that in the middle and top positions.…”
Section: A B Csupporting
confidence: 53%
See 2 more Smart Citations
“…Vessel cell portion tended to increase from the bottom culm to the top culm position. Darwis et al (2020) reported a similar trend in G. pruriens, with an increase in the parenchyma percentage from the outer to the inner part and vice versa for the vascular bundles. They also reported that parenchyma percentage in the bottom position was lower than that in the middle and top positions.…”
Section: A B Csupporting
confidence: 53%
“…Other research from India found that the longest fiber in the culm of Bambusa mizorameana was in the middle position and the shortest was in the bottom position (Kumar et al 2017). In G. pruriens, the fiber length was reported to be the shortest in the inner and bottom of the culm (Darwis et al 2020). The vessel diameter of the outer part of Gigantochloa bamboo ranged from 173.1 µm to 308.1 µm (Table 5).…”
Section: Cells Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…xinwuense [15][16][17]. We re-sequenced the whole genomes of these four bamboo species simultaneously and compared them with the P. edulis reference genome.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, P. edulis 'Pachyloen', P. nidularia f. farcta, and P. heteroclada f. solida are members of the genus Phyllostachys, with distinctly thickened culm walls that are 1-2 times thicker than S. dumetorum var. xinwuense [15][16][17]. We re-sequenced the whole genomes of these four bamboo species simultaneously and compared them with the P. edulis reference genome.…”
Section: Introductionmentioning
confidence: 99%